1963
DOI: 10.1126/science.141.3581.634
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating: Fictitious Results with Mollusk Shells

Abstract: Evidence is presented to show that modern mollusk shells from rivers can have anomalous radiocarbon ages, owing mainly to incorporation of inactive (carbon-14-deficient) carbon from humus, probably through the food web, as well as by the pathway of carbon dioxide from humus decay. The resultant effect, in addition to the variable contributions of atmospheric carbon dioxide, fermentative carbon dioxide from bottom muds, and, locally, of carbonate carbon from dissolving limestones, makes the initial carbon-14-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…The D 14 C value for the intermediate fraction is merely an index of reliability for the inner fraction D 14 C as are the inner and the intermediate fraction δ 13 C values. For uncontaminated marine samples, δ 13 C must be higher than -3‰ (Keith and Anderson 1963).…”
Section: Resultsmentioning
confidence: 99%
“…The D 14 C value for the intermediate fraction is merely an index of reliability for the inner fraction D 14 C as are the inner and the intermediate fraction δ 13 C values. For uncontaminated marine samples, δ 13 C must be higher than -3‰ (Keith and Anderson 1963).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the 1 4 C signal of riverine POC is significantly depleted with respect to current atmospheric values with ages reaching thousands of years, as it originates from old soil horizons, sedimentary fossil, sorbed petroleum and petroleum byproducts, and sewage sludge (Raymond and Bauer 2001). ô 1 3 C Anodonta anatina tissue values near -30%o are consistent with organic terrestrial food sources (Keith and Anderson 1963).…”
Section: Bivalve Tissue-shell14cmentioning
confidence: 86%
“…The only specimen (R-01), of Unio tumidus from a lacustrine location (Rosenfeld), presents an older tissue than shell age by over 150 yr ( (Keith and Anderson 1963;Rea and Colman 1995). Keith and Anderson (1963) hypothesized that more depleted ô 13 C values in lacustrine bivalve shells reflect the incorporation into DIC of C0 2 produced by fermentation of bottom muds that have ô 13 C values of approximately -5%o.…”
Section: R Fernandes Et Almentioning
confidence: 99%
“…Exchange of carbon isotopes has been the object of numerous studies (KEITH and ANDERSON, 1963;CHAPEL and POLACH, 1972;GRANT-TAYLOR, 1972;MANGERUD, 1972;MANGERUD and GULLIKSEN, 1975;THOM, 1972;THOMMERET, 1976;HILLAIRE-MARCEL and OCCHIETTI, 1977) and constitute an important source of error in shell age determination; the true age is increased if the exchange involves fresh water from calcareous springs or decreased -and this is the more frequent case -by the action of running water containing carbonic acid from the air. It has also been shown that the contaminations by isotopic exchanges are enhanced by the crystal structure: aragonite being far less susceptible to ionic substitution than calcite; in fact an X-Ray diffractogram is sufficient to be able to reveal tests containing recrystallized or foreign calcite.…”
Section: Methodology Of the Radiocarbon Measurementsmentioning
confidence: 99%